APPLICATION OF SAR REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEMS (GIS) IN COASTLINE CHANGE STUDIES – A CASE STUDY OF COASTLINE CHANGE DUE TO THE 2018 TSUNAMI IN TANJUNG LESUNG, BANTEN - Fuad, M. Arif Zainul; Effendi, Viola Rizka; Dewi, Citra Satrya U. (Asian Journal of Aquatic Sciences, 2022)
On December 22, 2018, a tsunami was triggered by a landslide from the eruptive material of Mount Krakatau which hit Tanjung Lesung Beach, Tanjung Jaya Village, Panimbang District, Pandeglang Regency, Banten Province. The disaster caused damage to infrastructure, changes in coastline, and claimed lives and property. This study aims to determine the changes in the Tanjung Lesung coastline due to the Tsunami. The data used is Sentinel-1 Satellite imagery which was acquired before and after the disaster, which was on 19 and 23 December 2018 respectively. Image processing was carried out on the Sentinel Application Platform (SNAP). The shoreline delineation utilizes the tracing technique in Arc-GIS. Calculation of shoreline changes using Digital Shoreline Analysis System (DSAS) tools with a Net Shoreline Movement (NSM) approach with the length and width of the transect line of 300 and 50 meters, respectively. The results showed that the shoreline changes that occurred were dominated by abrasion with the highest value of 18.89 m located on the west coast of Tanjung Lesung in Tanjung Jaya Village, Panimbang District, Pandeglang Regency. In addition, there is also accretion in the eastern area of ​​Tanjung Lesung Beach, although it only occurs in a small area with a coastline extension of 10.41 m.